Larval and juvenile fish assemblages in the sandy beach surf zones of Nanji Island, China - Wang, Xiaodong; Zhao, Dubin; Liu, Qiang; Lu, Tianyu; Zhong, Junsheng; Chen, Wandong; Xie, Shangwei; Chen, Shun (Frontiers in Marine Science, 2025)
The Nanji Islands, a nationally protected marine reserve in China, support high biodiversity but face significant fishery resource depletion. This study aims to describe the community structure of larval and juvenile fishes in the surf zone, a critical nursery habitat, to provide baseline data for conservation and management. Monthly surf zone sampling was conducted at five stations around Nanji Island from March 2023 to February 2024. Samples were collected during daytime (8:00-17:00) using a seine net (1×4m, 1mm mesh) with three replicates per station. A total of 8,568 fish were collected, representing 35 species from 21 families. The community was dominated by postflexion larvae (89.41%). Engraulidae was the most abundant family, with Engraulis japonicus constituting 91.30% of all specimens. Species number and catch per unit of effort (CPUE) peaked in August (16 species) and May, respectively, with minimal abundances from December to March. All diversity indices were highest in August and lowest in January. Cluster analysis of the data from 12 months indicated a strong, though not statistically significant, ecological pattern of community separation. The five stations were divided into western and eastern clusters. The species number, Margalef’s richness index, and Shannon–Wiener’s diversity index showed a positive correlation with temperature, but salinity showed a negative correlation with species number, CPUE and Shannon–Wiener’s diversity index. Niche partitioning observed between surf zone and open sea species in the Nanji Islands indicates that the surf zone acts as a specialized nursery for a subset of species (e.g., Engraulis japonicus and Lateolabrax maculatus), as opposed to a general habitat for all larval and juvenile fishes. The research contributes essential data necessary for the conservation and sustainable management of Nanji Island’s fisheries.